Outcomes in locally advanced rectal cancer with highly selective preoperative chemoradiotherapy. Issue 10 (12th June 2014) - Williamson, J S; Jones, H G; Davies, M; Evans, M D; Hatcher, O; Beynon, J; Harris, D A; ,
Abstract: Background: This study compared outcomes after surgery alone for stage II/ III rectal cancer in a tertiary cancer unit versus highly selective use of preoperative chemoradiotherapy (CRT). Methods: This was a single-centre retrospective cohort study of consecutive patients receiving potentially curative surgery for stage II and III primary rectal cancer. CRT was given only for magnetic resonance imaging-predicted circumferential resection margin (CRM) involvement and nodal disease (at least N2). Primary endpoints were CRM involvement and local recurrence rates. Secondary endpoints were systemic recurrence and overall survival. Data were analysed by log rank test, and univariable and multivariable analysis. Results: Between 2002 and 2012, 363 patients were treated for rectal cancer. After applying exclusion criteria, 266 patients with stage II/III mid or low rectal cancer were analysed. Of these, 103 received neoadjuvant CRT and 163 proceeded directly to surgery, seven of whom required postoperative radiotherapy; the latter patients were included in the neoadjuvant CRT group for analysis. There was a significant difference in local recurrence between the CRT and surgery-alone groups (6·5 versus 0 per cent at 5 years; P = 0·040), but not in CRM involvement (7·2 versus 5·1 per cent; P = 0·470), 5-year systemic recurrence (37·2 versus 43·0 per cent; P = 0·560) and overall survival (64·2 versus 64·6 per cent; P = 0·628) rates. Metastatic disease developed more frequently in low rectal cancers (odds ratio 0·14; P < 0·001), regardless of whether neoadjuvant treatment was delivered. Conclusion: Locally advanced rectal cancer does not necessarily require neoadjuvant CRT. Abstract : Is radiotherapy always needed?